The Relationship between Self-Esteem and Emotional Intelligence of Adolescent Students at SMP Negeri 1 Gorontalo City - Yusuf, Nur Ayun R.; Katili, Ansar; Bahsoan, Ismi Rahmatia (Universitas Negeri Gorontalo, 2024)
Introduction: Socio-emotional changes are often faced by adolescents. Therefore, they need. Good emotional intelligence to be able to control them selves and get through adolescence well. One of the factors that most influences emotional intelligenceis self-esteem. Objective: This study aims to know the relationship between self-esteem and emotional intelligence. Method: This is a quantitative descriptive study using survey method and cross-sectional approach. The populationis 1014 students with the sample of 287 students take nusing cluster sampling technique. Result: The finding shows that most of the respondents' self-esteem is in the low category with a total of 146 students (50.9%), while most of their emotional intelligenceis in the medium category with a total of 141 students (49.1%). The Spearman Rank Testresults show p-value = 0.000 (